PENGARUH PERMAINAN DADU PUTAR TERHADAP LITERASI BAHASA ANAK USIA 5-6 TAHUN - Salsabila Shofiyah; Nur Ika Sari Rakhmawati; Ruqoyyah Fitri; Dhian Gowinda Luh Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Dadu Putar (Spinning Dice) educational game on the language literacy skills of children aged 5–6 years at TK Negeri Pembina Surabaya. The study employed a quantitative approach using a quasi-experimental design with a nonequivalent pretest–posttest control group design. The research involved 29 children divided into an experimental group and a control group through purposive sampling. Data were collected using observation, tests, and documentation, while data analysis included validity, reliability, normality, homogeneity, and hypothesis testing using SPSS. The findings revealed that children's language literacy skills improved after the implementation of the Dadu Putar game. The experimental group's average achievement increased from 49.11% on the pretest to 80.36% on the posttest. The paired sample t-test showed a significance value of 0.000 (p < 0.05), indicating a significant difference between pretest and posttest scores. The results demonstrate that the Dadu Putar educational game has a positive and significant effect on improving children's language literacy skills, particularly in recognizing vowels, distinguishing similar letters, and reading simple words. Therefore, the Dadu Putar game can serve as an effective and engaging learning medium for early childhood language literacy development.